ANALYSIS OF INTRINSIC ELEMENTS IN SHORT STORIES BY WIDYA SUWARNA - Aisyah Putri Muhandra; Anniza Nursyahbani Siregar; Rizky Pratiwi; Hamidah Siloto; Diana Sopha (Fakultas Sastra UMN AL Washliyah, 2023)
This study aims to analyze the intrinsic elements in short stories by Widya Suwarna in terms of meaning and language. There are three titles of short stories analyzed namely“When the Sea is Angry”, “Calendar Mia Made”,and